Striving for Open Access publishing at KTH Royal Institute of Technology: Are we on the right track? - Dubus, Gaël; Fathli, Margareta (Septentrio Conference Series, 2022)
Open Access publishing (OA) has been promoted by public institutions and research communities in many countries for some years now. Various categories encompassing different types and practices of OA are precisely described in definitions that now seem to be well-established. OA status is now available as part of a publication's metadata in all major publication databases, while some data sources such as Unpaywall are specifically dedicated to this type of information. At KTH, we monitor and document the effects of this shifting landscape and of policies promoting OA by means of an annual OA report focused on scientific publications by our researchers. This allows us to observe potential effects of KTH policy changes and to identify areas that the KTH management or the KTH library could support or strengthen. To this end, we collect the OA status (open, closed) and OA type (gold, diamond, hybrid, green) from Unpaywall for several publication types (journal articles, conference proceedings, theses, book chapters) and aggregate these data both for KTH as a whole and for each of its five schools. We also identify the journals in which KTH researchers publish the most and calculate the OA proportion of KTH publications in these. Finally, we take a look at the evolution of publishing-related costs for KTH and KTH schools and relate them to changes in the university's publishing policy. Results show that the OA share of KTH peer-reviewed publications has been globally increasing since 2011, strongly so for theses and journal articles. This is mainly due to the increase of gold and hybrid OA, despite the fact that journals where KTH authors publish the most are still mainly subscription-based. The increase in OA share is less pronounced for conference proceedings but nonetheless steady. A diversity of publishing practices in different research areas is revealed by the different OA publishing patterns at the different KTH schools. An overall increase in Article Processing Charges (APC) can be observed, related to both the increase of the number of hybrid and gold OA publications and to the implementation of new transformative agreements with several publishers. We discuss the consequences of the current university policy and compare it to alternative policies supporting OA while limiting the increase of publishing costs. We also reflect upon the extent to which researchers can be guided towards better OA practices and the role a university library may play in the process. Considering the questions of sustainability in a foreseeable future and of equity in the scientific publishing landscape paramount, we strongly value input from various actors within open science communities in order to build a sound reference framework for OA-supporting policies.